Cooking up a revolution : Food Not Bombs, Homes Not Jails, and resistance to gentrification - Parson, Sean (Book collections on Project MUSE., 2019)
During the late 1980s and early 1990s the City San Francisco waged a war with the homeless. During this period over 1,000 arrests and citations where handed out by the police to activists for simply handing out free food in public parks. Why would a liberal city arrest activists helping the homeless? In exploring this question, the book uses the conflict between the city and activists as a unique opportunity to examine the contested nature of urban politics, homelessness, and public space while developing an anarchist alternative to liberal urban politics that is rooted in mutual aid, solidarity, and anti-capitalism. In addition to exploring theoretical and political issues related to gentrification, broken-windows policing, and anti-homeless laws, this book provides both activists, students, and scholars, examples of how anarchist homeless activists in San Francisco resisted these process.